The global burden of colorectal cancer attributable to high plasma glucose in 204 countries and territories, 1990–2019: an analysis of the Global Burden of Disease Study. (April 2023) - Yang, Bin; Lv, Youyou; Shi, Oumin; Yan, Mengqing; Li, Xiao; Kang, Wenjun; Yang, Yongli; Wang, Wei; Wang, Qi
Abstract: Objectives: This study aimed to estimate the burden of colorectal cancer (CRC) attributable to high plasma glucose from 1990 to 2019. Study design and methods: Data on the disease burden were retrieved from the Global Burden of Disease online database. Estimated average percentage change (EAPC) was used to quantify the age-standardized mortality rate (ASMR) and age-standardized disability-adjusted life years (DALYs) rate (ASDR) of high plasma glucose–related CRC trends by sex and location between 1990 and 2019. Results: Globally, the death number and DALYs of CRC attributable to high plasma glucose remained a steady increase at global level from 1990 to 2019, and similar trends have been reported in age-standardized rate. The country with the largest number of death cases and DALYs of high plasma glucose–related CRC in 2019 was China, followed by the United States of America and India. Nearly three-quarters of total countries experienced an increase in the ASMR and ASDR, and the greatest increase of ASMR and ASDR was found in Uzbekistan (EAPC = 5.32) and Equatorial Guinea (EAPC = 4.65), respectively. A negative correlation was found between sociodemographic indices and the EAPC of ASMR and ASDR ( r ASMR = −0.259, p < 0.001; r ASDR = −0.282, p < 0.001). Conclusions: A significant increase in mortality and DALYs of CRC attributable to high plasma glucose was observed in global and most countries, especially in the developing countries. Public health policies and targeted programs are needed to reduce the burden of disease.